The Effect of Learning Cycle Model with Approach (SAVI) on Student Activities at SMAN 1 Ampek Angkek - Khairani, Majidah (JMEA : Journal of Mathematics Education and Application, 2020)
This study aims to determain the ability of SAVI approach effect  to ability of activity in matemathical learning in class X SMAN 1 Ampek Angkek. The study was a pre-experimental whit the one shot case study design. The subjects of this rearch were students in class X SMAN 1 Ampek Angkek. The research subjecthe results are given treatment that is making a learning Cycle whit  SAVI approach on the learning process. The data of this research obtained  in the from of value the abilty to make learning Cycle whit  SAVI approach, the value of ability to activity in matemathical learning in class X SMAN 1 Ampek Angkek. The research is a correlational research. The population of this study were all students of class X SMA N 1 Ampek Angkek. The data were analiyzed by regression analysis. The results show that there is an influence of activity-based learning students  = 47.19 + 1.284 X, and determination R2 = 41,7 %. This means, 41,7 % of the total variation in the ability of activity based learning students.